Pengaruh Sistem Pengetanahan Terhadap Arus Gangguan Tanah Pada Sistem Distribusi 20 Kv Di PLN Palur Dengan Menggunakan Etap 12.6 - Pangeran Alfidin, Mohammad; , Agus Supardi, S.T., M.T (2016)
PT. PLN Rayon Palur is the electric company which is engaged in distribution of electrical energy and maintenance of the electrical grid to consumers. In the process of distribution of electrical energy, a fault is often recurred, one of them is a ground fault. Ground fault consisting of single phase to ground fault and two phase to ground fault. Ground fault current will changes the settings of ground fault relay ( GFR ). To overcome this, it is necessary to analyze ground fault. This research will analyze the influence of grounding system to ground fault currents, this research began by studying literature, data collection, modeling of 20 kV distribution network with ETAP, analysis of ground fault, make conclusions from the analysis performed. The results showed there is influence of the type of grounding, the values of grounding impedance, and the location of ground fault to the ground fault current. Type of ground solid gained ground fault current value is large, because without enter an impedance value. The smaller the impedance the large the ground fault current. The farther the location the smaller the ground fault current smaller and the closer the location the smaller the ground fault voltage. The time setting of GFR in the incoming 150 kV network is 0.2527 seconds and the time setting of GFR in outgoing network of 20 kV is 0.3229 seconds at Palur 19 feeder.